2020
DOI: 10.1186/s12883-020-01871-5
|View full text |Cite
|
Sign up to set email alerts
|

Recurrence and retreatment of anterior communicating artery aneurysms after endovascular treatment: a retrospective study

Abstract: Background S urgical treatment of anterior communicating artery (Acom) aneurysm is challenging due to anatomic complexity. We aimed to describe our experiences with endovascular treatment (EVT) of Acom aneurysms, and to evaluate the incidence and risk factors of recurrence and retreatment. Methods The study comprised 260 patients who were treated at a single center between January 2010 and December 2018. Patients who had EVT, including stent-assisted coil… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
15
1
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 44 publications
(39 reference statements)
1
15
1
1
Order By: Relevance
“…A study reporting a 9-year experience of ruptured ACoA aneurysms, published in 2017, found a similar retreatment percentage of only 10%; that study also found that 79% of patients had an mRS score of <3 on follow-up 15. Interestingly, in 2020, Jang et al analyzed 77 patients with ruptured ACoA aneurysms treated with coil embolization and found a similar 10% retreatment rate (n=8) 16. The mortality rate found in the present study was only 10% (19/186), which is consistent with earlier endovascular literature (10%–31%) 17–19.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…A study reporting a 9-year experience of ruptured ACoA aneurysms, published in 2017, found a similar retreatment percentage of only 10%; that study also found that 79% of patients had an mRS score of <3 on follow-up 15. Interestingly, in 2020, Jang et al analyzed 77 patients with ruptured ACoA aneurysms treated with coil embolization and found a similar 10% retreatment rate (n=8) 16. The mortality rate found in the present study was only 10% (19/186), which is consistent with earlier endovascular literature (10%–31%) 17–19.…”
Section: Discussionmentioning
confidence: 95%
“…Park et al found that incomplete occlusion is a significant risk factor for recurrence (odds ratio (OR) 2.72, P=0.02) 23. Similarly, Jang et al reported that class II and III occlusions were significantly associated with retreatment rate (OR 6.19, P=0.03) 16…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…8 The asymmetry in the CoW raises wall shear stress and may play a critical role in the development and recurrence of cerebral aneurysms after treatment. [9][10][11][12] This risk increases with the degree of flow contribution from the 2 adjacent anatomical segments of the CoW. This difference may result from the actual difference in the artery diameters, or it may be due to variation in the blood flow among the carotid and basilar arteries across the ACoA and PCoA.…”
Section: Introductionmentioning
confidence: 99%
“…(2020) сообщили, что частота рецидивирования аневризм передней соединительной артерии после их окклюзии спиралями, в том числе с использованием стент-ассистенции, может достигать 14,6%, а необходимость в повторном вмешательстве -3,8% [5].…”
unclassified